Acupuncture and other traditional Chinese medicine therapies in the treatment of children’s tic syndrome: A network meta-analysis - Pu, Tong; Liu, Yu; Wang, Junxia; Zhang, Jieying; Zhang, Jinhao; Ran, Zhiling; Sheng, Qiaoni; Yi, Zhiqiang; Ye, Jiansong; Li, Yanling; Wang, Xijun; Chi, Hao; et al. (Frontiers in Neuroscience, 2023)
Abstract Background: Tic disorders (TD) are a kind of neuropsychiatric diseases that frequently occur in preschool and school age, mainly characterized by motor tics or sometimes accompanied by vocal tics, and its pathogenesis is still unclear. The clinical manifestations are mainly characterized by chronic multiple movements, rapid muscle twitching, involuntary occurrence and language disorder. Acupuncture, tuina, traditional Chinese medicine and other methods are commonly used in clinical treatment, which have unique therapeutic advantages, but have not been recognized and accepted by the international community. This study conducted a quality evaluation and meta-analysis of the currently published Randomized controlled trials (RCTS) of acupuncture for TD in children, in order to provide reliable evidence-based medical evidence for acupuncture for TD. Methods: All the randomized controlled trials (RCTS) in which the intervention methods were (acupuncture + traditional Chinese medical herbs), (acupuncture + tuina), and acupuncture, and the control group was commonly used western medicine were included in the analysis. The main outcomes were Yale Global Tic Severity Scale (YGTSS) scale, Traditional Chinese medicine (TCM) syndrome score scale, and clinical treatment efficiency. Secondary outcomes included adverse events. The risk of bias of the included studies was assessed according to the tool recommended by Cochrane 5.3. The risk of bias assessment chart, risk of bias summary chart and evidence chart in this study will be produced using R and stata software. Results: There were 39 studies that met the inclusion criteria, including 3038 patients. In terms of YGTSS, TCM syndrome score scale changes and clinical effective rate, acupuncture combined with Chinese medicine is the best treatment. Conclusion: (Acupuncture + traditional Chinese medical herbs) may be the best therapy to improve TD in children. At the same time, compared with western medicine commonly used in clinical practice, acupuncture and acupuncture combined with tuina therapy have better effects on improving TD in children.